Intralobar bronchopulmonary sequestration: antenatal diagnosis. Issue 4 (April 1994) - Ng, K J; Hasan, N; Gray, E S; Jeffrey, R R; Youngson, G G
Abstract : A child with the antenatal diagnosis of pulmonary cystic adenomatoid malformation underwent thoracotomy and an intralobar bronchopulmonary sequestration was found. Histological examination of the resected specimen showed cystic adenomatoid malformation within the sequestered segment.